Implementation of Zero Client Network Using vCloudPoint at PT XYZ with Action Research Method - Kristiyanto, Yogi; Sismadi, Wawan; Susanto, Yodi (RISTEC : Research in Information Systems and Technology, 2024)
This study aims to implement a Zero Client network using vCloudPoint devices at PT XYZ using the Action Research method. The purpose of this study is to improve operational efficiency and information technology management in the company through an iterative approach involving planning, action, observation, and reflection. The method used allows for continuous improvement during the implementation process. The results of the study indicate that the implementation of Zero Client can reduce IT infrastructure costs, improve system stability, and facilitate device management through a centralized server using Windows Server 2019 and vMatrix vCloudPoint. Network devices such as Ruijie routers and switches support reliable connectivity to distribute data efficiently. This study concludes that the implementation of Zero Client provides an effective solution to improve productivity and operational efficiency at PT XYZ. These findings provide a basis for further research on the development of a broader Zero Client model and its integration with the latest security technologies